P117: A multicenter analysis of an emergency physician lead on department flow and the provider experience. (May 2020) - Crowder, K.; Domm, E.; Lipp, R.; Robinson, O.; Vatanpour, S.; Wang, D.; Lang, E.
Abstract : Introduction: Emergency department (ED) flow is a strong predictor of patient safety, quality of care and provider satisfaction. Throughput interventions have been shown to improve flow metrics, yet few studies have considered MD leadership roles and evaluated provider experience. Our objective was to evaluate the emergency physician lead (EPL) role, a novel MD staffing initiative. Methods: This mixed-method observational time series analysis evaluated ED metrics at two tertiary EDs including ED length of stay (LOS), EMS Park LOS and physician initial assessment (PIA) time as well as 72-hour readmit and left without being seen (LWBS) rates. Data was collected from the ED information system database for control (Dec 6, 2017-Feb 28, 2018 SITE1 and Mar 1–May 31, 2018 SITE2), pre (Sept 3-Nov 30, 2018 SITE 1 and Dec 3, 2018-Feb 28, 2019 SITE2) and post (Dec 3, 2018 –Feb 28, 2019 SITE1, Mar 1- May 31, 2019 SITE2) periods for adult patients presenting to each site. Site data was analyzed independently using descriptive and inferential statistics to calculate differences in means, and means were compared using t-tests. A survey elicited provider feedback from ED physicians, nurses, and EMS professionals on the effect of the EPL on throughput, timeliness of admissions and discharges, provider workload, and the EPL as a resource to other professionals. Results: The number of ED visits at SITE1 were 13136 (Ctrl), 13236 (Pre) and 13137 (Post), and at SITE2 were 14371(Ctrl), 13866 (Pre) and 14962 (Post). Mean ED LOS was decreased by 17 min in post vs control and 20 min vs pre at SITE1 (p < 0.01). SITE2 saw an increase in ED LOS by 7 min vs control and 8 min vs pre (p < 0.01). EMS LOS at SITE1 was decreased by 21 min vs control and 22 min vs pre (p < 0.01), but was increased at SITE2 by 2 min vs control (p = 0.09) and 14 min vs pre (p < 0.01). PIA time at SITE1 was decreased by 15 min vs control (p < 0.01) and 13 min vs pre and increased by 5 min vs control and 12 min vs pre at SITE2 (p < 0.01). 72 hour readmit and LWBS rates were unchanged at both sites. Qualitative feedback from ED providers highlighted the early provision of treatments and investigations by the EPL, and many felt the EPL was an important resource. Conclusion: The inclusion of both quantitative and qualitative data in this study provided a robust analysis of the impact of the EPL role and demonstrated modest but important improvements. A site-dependent, carefully considered implementation of the EPL role may improve ED metrics and provider experiences.